2013
DOI: 10.3390/molecules181113435
|View full text |Cite
|
Sign up to set email alerts
|

Polyphenolic Extracts of Edible Flowers Incorporated onto Atelocollagen Matrices and Their Effect on Cell Viability

Abstract: Abstract:The phenolic extract of chives flowers (Allium schoenoprasum, Liliaceae), introduced Sage (Salvia pratensis, Lamiaceae), European elderberry (Sambucus nigra, Caprifoliaceae) and common dandelion (Taraxacum officinale, Asteraceae) were characterised by High Performance Liquid Chromatography and incorporated in different concentrations onto atelocollagen thin films. In order to assess the biological impact of these phenolic compounds on cell viability, human immortalised non-tumorigenic keratinocyte cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
1

Year Published

2015
2015
2025
2025

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 46 publications
0
19
1
Order By: Relevance
“…However, the same study was unable to demonstrate any activity in either the methanol or water extract against S. aureus. A more recent study by López-García et al (2013) reported that an aqueous methanol (90% v/v) extract of dandelion flowers demonstrated no inhibition of bacterial growth against S. aureus and E. coli despite identifying a number of phenolic compounds (i.e. gallic acid, rutin, resveratrol, vanillic acid and sinapic acid) in this extract.…”
Section: Antimicrobial Activity Of Crude and Dialysed Extractsmentioning
confidence: 83%
See 1 more Smart Citation
“…However, the same study was unable to demonstrate any activity in either the methanol or water extract against S. aureus. A more recent study by López-García et al (2013) reported that an aqueous methanol (90% v/v) extract of dandelion flowers demonstrated no inhibition of bacterial growth against S. aureus and E. coli despite identifying a number of phenolic compounds (i.e. gallic acid, rutin, resveratrol, vanillic acid and sinapic acid) in this extract.…”
Section: Antimicrobial Activity Of Crude and Dialysed Extractsmentioning
confidence: 83%
“…Whilst the authors hypothesised that phenolic compounds were responsible for the observed activity, no compounds were identified. Contradictory to the study by Sengul et al (2009), López-García et al (2013 have since reported the inactivity of a similar extract against strains of Escherichia coli and Staphylococcus aureus, while also identifying several phenolic compounds including gallic acid, rutin, resveratrol, vanillic acid and sinapic acid. Although there appears to be some evidence for the antimicrobial efficacy of dandelion, there is a lack of clarity regarding the potency of this activity and indeed the compounds responsible.…”
Section: Introductionmentioning
confidence: 99%
“…Usually by mixing different ingredients, the diffraction bands existing in diffractograms sustain some attenuation, diminishing, scattering, and broadening, which are all clear indications of the crystallinity lowering. [32,47,166,174,211,235,239,240] Antibacterial activity is performed by the assessment of the zone of inhibition assay on a solid medium placed in Petri dishes and containing specific media for each microorganism tested [74,125,129,141,171,176,179,187,213,238,[241][242][243][244][245][246][247][248][249][250][251][252][253][254][255][256][257][258][259].…”
Section: X-ray Difractionmentioning
confidence: 99%
“…Contrarily, extracts of 130 and 200 mg/mL from aerial parts were unable to prevent the growth of 34 microorganisms from genera Bacillus, Enterobacter, Klebsiella, Listeria, Pseudomonas, Salmonella, Staphylococcus, Aspergillus, and Candida, among others; therefore, it was considered inactive at these concentrations in a disc diffusion assay [66]. A methanolic T. officinale flower extract was not active against E. coli or S. aureus at 1.0 mg/mL in a diffusion agar assay [62] and no activity was found on S. aureus, E. coli, P. aeruginosa, or C. albicans using a leaf ethanolic extract when 0.05 mL were placed in sterile discs [57]. Furthermore, an ethanolic extract of leaves displayed no activity against S. aureus, E. coli, or S. abony by the serial dilution method [58], with the same results for root and leaf extracts on M. aurum and M. smegmatis at 0.5 mg/mL [63].…”
Section: Human Pathogensmentioning
confidence: 99%